2007
DOI: 10.1152/japplphysiol.01077.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple trait measurements in 43 inbred mouse strains capture the phenotypic diversity characteristic of human populations

Abstract: The breadth of genetic and phenotypic variation among inbred strains is often underappreciated because assessments include only a limited number of strains. Evaluation of a larger collection of inbred strains provides not only a greater understanding of this variation but collectively mimics much of the variation observed in human populations. We used a high-throughput phenotyping protocol to measure females and males of 43 inbred strains for body composition (weight, fat, lean tissue mass, and bone mineral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(168 citation statements)
references
References 27 publications
8
154
6
Order By: Relevance
“…In contrast to most other mouse lines, in which males express a higher phenotype than females, 28,29 BFMI860 females accumulated the same high amount of total fat mass and single adipose tissues as the males. Taking body weight into account, females had a higher total fat mass percentage than males.…”
Section: Phenotypes Of Parental Lines F 1 and F 2 Animalscontrasting
confidence: 65%
“…In contrast to most other mouse lines, in which males express a higher phenotype than females, 28,29 BFMI860 females accumulated the same high amount of total fat mass and single adipose tissues as the males. Taking body weight into account, females had a higher total fat mass percentage than males.…”
Section: Phenotypes Of Parental Lines F 1 and F 2 Animalscontrasting
confidence: 65%
“…Additional strain selection: Using the Paigen2 mouse strain set (Svenson et al 2007) from the Mouse Phenome Database as a starting point, we determined a new set of 33 inbred strains that would provide an increase in power when compared with the Paigen2 set. Our strain set was selected by first removing both wild-type and some genetically similar strains from the original Paigen2 strain set of 42 strains [for high-density lipoprotein (HDL) cholesterol].…”
Section: Imputation Of Missing Genotypesmentioning
confidence: 99%
“…This suggested that the LDLR directs apoB to degradation through an ER-associated pathway. To test this result in a more physiological system, we used a newly generated hypercholesterolemic mouse obtained from an ethyl-nitrosourea mutagenesis screen with high throughput phenotyping (24). The hypercholesterolemia in this mouse results from a mutation in the Ldlr gene leading to a C678Y amino acid substitution (numbering excludes the 21-amino-acid signal peptide).…”
Section: The Ldlr Regulates Apob Secretion Through a Post-ermentioning
confidence: 99%